WiFi offloading using the device-to-device (D2D) communication paradigm based on the Software Defined Network (SDN) architecture. (15th June 2018) - Cheng, Rung-Shiang; Huang, Chung-Ming; Pan, Sheng-Yuan
Abstract: WiFi offloading is a commonly used technique for reducing the traffic load in 3G/4G/5G cellular networks. The offloading process is normally infrastructure-based, i.e., the offloaded traffic is routed through a WiFi AP. If two communicating mobile nodes are connected to the same AP, the potential exists to improve the networking performance by having the two mobile nodes to communicate with each other over a WiFi Device-to-Device (D2D) link rather than through the AP. However, realizing such a WiFi D2D-based offloading approach needs to solve two fundamental problems, namely (1) determining whether the two mobile nodes can have D2D communications or not and (2) deciding when the two mobile nodes using the D2D communication mode should revert to the AP-based WiFi infrastructure communication paradigm. This study proposes a Software Defined Network (SDN)-based control scheme for resolving the aforementioned two issues. The simulation results show that the proposed scheme can achieve a significant improvement in the WiFi offloading performance compared with using the pure infrastructure-based offloading approach.